(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
This paper aims to study the contributions of Antoine Arnold and Pierre Nicole, who known as Port-Royal logicians, in terms of the theory of ideas at the cognitive-epistemological and logical levels. By thoroughly addressing the answers provided about the origin, nature, source, structure, implication and different classification of ideas, which traditionally belong to the tTheory of knowledge, this paper attempts to focus on the contents and logical references related to the research of terms, their types, intension, extension, and relationship to language, categories, predicable or the Five Universals, underscoring the interactions between the two levels, and the new additions presented. By engaging in such examination, argues that Arnold’s and Nicole’s contribution is an attempt to revival of the traditional logic paradigm and a demonstration of it in terms of Cartesian’s theory of knowledge, in a way different from what has prevailed in that era where there has been an attempt to break with this paradigm and work towards establishing new paradigms.